Genome-Wide QTL Mapping for Stripe Rust Resistance in Winter Wheat Pindong 34 Using a 90K SNP Array - Zhou, Xinli; Li, Xin; Han, Dejun; Yang, Suizhuang; Kang, Zhensheng; Ren, Runsheng (Frontiers in Plant Science, 2022)
Winter wheat cultivar Pindong 34 has both adult-plant (APR) resistance and all-stage resistance (ASR) to stripe rust, which is caused by Puccinia striiformis f. sp. tritici (Pst). To map the quantitative trait loci (QTL) for stripe rust resistance, an F6-10 recombinant inbred line (RIL) population from a cross of Mingxian 169 × Pingdong 34 was phenotyped for stripe rust response over multiple years in fields under natural infection conditions and with selected Pst races under controlled greenhouse conditions, and genotyping was performed with a 90K single nucleotide polymorphism (SNP) array chip. Inclusive composite interval mapping (ICIM) identified 12 APR resistance QTLs and 3 ASR resistance QTLs. Among the 12 APR resistance QTLs, QYrpd.swust-1BL (explaining 9.24–13.33% of the phenotypic variation), QYrpd.swust-3AL.1 (11.41–14.80%), QYrpd.swust-3AL.2 (11.55–16.10%), QYrpd.swust-6BL (9.39–12.78%), QYrpd.swust-6DL (9.52–16.36%), QYrpd.swust-7AL (9.09–17.0%) and QYrpd.swust-7DL (8.87–11.38%) were more abundant than in 5 of the tested environments and QYrpd.swust-1AS (11.05–12.72%), QYrpd.swust-1DL (9.81–13.05%), QYrpd.swust-2BL.1 (9.69–10.57%), QYrpd.swust-2BL.2 (10.36–12.97%) and QYrpd.swust-2BL.3 (9.54–13.15%) were significant in some of the tests. The three ASR resistance QTLs QYrpd.swust-2AS (9.69–13.58%), QYrpd.swust-2BL.4 (9.49–12.07%) and QYrpd.swust-7AS (16.16%) were detected based on reactions in the seedlings tested with the CYR34 Pst race. Among the 15 QTLs detected in Pindong 34, the ASR resistance gene QYrpd.swust-7AS mapped on the short arm of chromosome 7A was likely the same to the previously reported QTL Yr61 in the region. The QTLs identified in the present study and their closely linked molecular markers could be useful for developing wheat cultivars with durable resistance to stripe rust.